Creative Destruction and Asset Prices - Grammig, Joachim; Jank, Stephan (Journal of Financial and Quantitative Analysis, 2016)
We relate Schumpeter’s notion of creative destruction to asset pricing, thereby offering a novel explanation of size and value premia. We argue that small-value firms must offer higher expected returns to compensate for the risk posed by serendipitous invention activity, whereas large-growth stocks provide protection against creative destruction and receive expected return discounts. A 2-factor model that accounts for creative-destruction risk effectively explains the cross-sectional return variation of size- and book-to-market-sorted portfolios. The estimated risk compensations associated with creative destruction are substantial and statistically significant, indicating their relevance for asset pricing.